The Influence of a Digital-Based Curriculum on Learning Motivation : (A Case Study of Driving Schools in the Papua Pegunungan Province) - Roberto W. Marpaung (Badan Penerbit STIEPARI Press, 2025)
The study was conducted in Papua Mountains Province, faces unique challenges in implementing a digital-based curriculum. Geographical factors and limited access to technological infrastructure are important aspects influencing the effectiveness of implementing a digital learning system. The research was a quantitative research, and the research design was a causal research design used to prove the relationship between cause and effect of several variables. Causal research usually uses the ex-post facto method, namely by controlling independent variables that will affect dependent variables in planned situations. The analysis tool used is SPSS 2025 with an ordinal measurement scale of 1-5. With a sample of 30. The results of the hypothesis test using the t-test, obtained a t-count value of 21.273 with a significance value of 0.000. So it can be concluded that the effect of implementing a digital-based curriculum has a positive and significant effect on learning motivation.